Pola Pendidikan Orangtua dan Perkembangan Sosio Emosional Anak Berdasarkan Amsal 4:1-27 - Sulistyowati Sulistyowati; Farel Yosua Sualang (Sekolah Tinggi Teologi Injili Indonesia Samarinda, 2025)
This study examines parenting patterns and their relationship to children's socio-emotional development through an expository analysis of Proverbs 4:1–27. The Book of Proverbs offers wisdom principles relevant to shaping a child's character, morality, and emotional stability, emphasizing the role of parents as primary educators. The research method used is biblical exposition with a qualitative approach through literature study and textual analysis. The findings reveal that parental education includes loving discipline, consistent life example, constructive communication, and the instillation of moral and spiritual values. Balanced discipline supports healthy emotional regulation in children, while parental example provides a tangible model of wise behavior. Effective communication fosters a sense of security and openness. This study affirms that wisdom-based education, as taught in Proverbs 4:1–27, serves as a practical guide for Christian parents in holistic child-rearing and contributes to the development of practical theology and Christian education.